ADOLESCENTS' RECEPTION OF KI BATA KI DUMONDALIO SONG AND ITS CONTRIBUTION TO COMMUNITY CHARACTER BUILDING: A CASE STUDY IN AMBANG 1 VILLAGE, BOLAANG MONGONDOW - Mokodongan, Thalia Celine Syarief; Al Katuuk, U. M. Kamaja; Loho, Joni J. (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This study aims to explain the reception of teenagers in Ambang 1 village, Bolaang Mongondow, towards the cultural values contained in the Bolaang Mongondow folk song entitled Ki Bata Ki Dumondaloi and describe the implications of the research results for the value of character education in the song. The research method used is qualitative with a literary reception approach. This research was conducted in Ambang 1 village, Bolaang Mongondow, and involved 16 teenagers as research informants. The results showed the following findings: 1) Of the 16 respondents, 13 of them had memorized the song Ki Bata Ki Dumondaloi. 2) Teenagers' reception of the meaning of the song lyrics showed that all respondents knew the meaning of the song lyrics. 3) Teenagers are able to perceive the implications of the song content and relate it to the current situation. 4) There are differences in the perception of the song content related to whether a girl can visit her boyfriend's house or not. 5) The majority of respondents perceived it with sadness if a girl came to her boyfriend's house and was scolded by the boyfriend's parents. 6) Some respondents perceived it based on the Mongondow customary rules that still apply, where a girl should not come to her boyfriend's house, while others perceived that it is allowed. Thus, the Bolaang Mongondow folk song Ki Bata Ki Dumondaloi has a contribution in shaping the character of Mongondow ethnic young women by emphasizing the values of manners, friendliness, and politeness in their relationships.